Organic light emitting diodes - new emissive materials and device architecture - Strevens, Adam (Trinity College (Dublin, Ireland). School of Physics, 2007)
Organic materials are now used for a variety of electronic devices including organic light-emitting diodes (OLEDs). However, most organic electronic display applications require more efficient red, green and blue OLEDs with improved lifetimes. Significant improvements are possible by developing better materials and device structures pertaining to charge-injection, -transport, -recombination and radiative exciton decay.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin